UJI AKTIVITAS ANTIOKSIDAN AIR MAWAR (Rose water) DARI PETAL BUNGA MAWAR MERAH (Rosa damascena Mill) MENGGUNAKAN METODE DPPH (Diphenyl Picril Hidrazil) - Yustina Wuri Wulandari; Sutardi Sutardi Sutardi (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Rose water was water that has a distinctive flavor of rose and produced from the extraction of red rose petals using the steam distillation method. Red rose flowers have been used by some people as food. The purpose of this study was to determine the antioxidant activity of red rose water extract using Diphenyl Picril Hidrazil (DPPH) at various extraction times. The research method consisted of extraction of rose water by steam distillation at a pressure of 2 bar, phytochemical test including phenolic and vitamin C analysis, and antioxidant activity tests. The results of the phytochemical test showed that the extraction time for rose water was 75 minutes, the highest phenolic compound content was 115.04 ± 0.52 mg GAE/g and the highest vitamin C content was 2.201,67±2,89 mg/ 100 g. Based on the IC50 value of rose water extract according to the extraction time successively at the 75 minute was 49.46 ppm; at the 150 minute was 108.36 ppm; at the 225 minute it was 120.22 ppm and the 300 minute it was 160.78 ppm. This shows that rose water is classified as having very strong to moderate antioxidant activity